Andrzej Dłużniewski’s Literature of Everyday Fragments - Lachman, Magdalena; Polit, Paweł ((Dif)fusions: Relations between Literature and Art in Poland after 1945, 2019)
The text is an attempt at discussing the literary dimension of Andrzej Dłużniewski’s artistic output – the way of combining by him the practice of Conceptual art with the construction of literary narratives. Referring to the tradition of ready-made, Dłużniewski used found elements – such as objects, pictures, linguistic expressions – as the carriers of particular stories, whose threads intermesh within a larger structure of references. In his works, the artist linked the visual elements with the linguistic ones, constructed narratives related to objects and pictures. He was the author of concise, sparkling with paradox, literary forms.